Effects of key factors on the compressive strength of metakaolin and limestone powder-based alkali-activated concrete mixtures: An experimental and statistical study. (June 2022) - Ahmad, Shamsad; Bahraq, Ashraf A.; Shaqraa, Abbas Albu; Khalid, Hammad R.; Al-Gadhib, Ali H.; Maslehuddin, Mohammed
Abstract: The present study aimed at utilizing locally available metakaolin (MK) and limestone powder (LSP) as base binders for developing alkali-activated concrete. Ordinary Portland cement (OPC) was used as a secondary binder. Specimens with different primary binder (MK or LSP), its content (70%, 85%, or 100%), activator type (NaOH- or KOH-based), and activator composition (sodium silicate/hydroxide ratio: 1, 2.5, or 4) were prepared, and tested for compressive strength. The obtained strength data were statistically analyzed using ANOVA and response surface methods (RSM) to explore the effects of the studied variables. Test results showed that all the considered parameters had significant effects on the tested properties where the effect of the primary binder content was more pronounced than the alkaline composition. Two mixtures (70% MK with sodium silicate/KOH ratio of 2.5 and 70% LSP with sodium silicate/KOH ratio of 4.0) showed more than 20 MPa strength, which can be categorized as structural concrete. While all the remaining mixtures exhibited less than 20 MPa strength. These can find non-structural applications such as backfill, footpath slab, or controlled low strength materials (CLSM).